Financing SMEs through the Islamic Qard al-Hasan: a proposal of Islamic FinTech interest- free lending for government initiatives. - Adam Sa'ad, Auwal; Pitchay, Allah Pitchay (IGI Global Publication, 2019)
Financing small and medium enterprises (SMEs) is one of the most important mechanisms to boost eco- nomic growth in both developed and developing nations. The contributions of SMEs in many countries’ gross domestic product (GDP) have been overwhelming. SMEs improve job creation in all sectors of the economy and contribute to the people’s economic wellbeing. However, many SMEs are not getting financing from their respective counties due to strict regulations and interest rate hike. With this kind of regulations and high interest, many brains are wasted, and many ideas are vanishing with the job opportunities attached them. Government agencies are therefore in need to innovate different ways to facilitate SME financing and support new businesses for achieving and maintaining sustainable economic growth. This chapter proposes an Islamic FinTech and its mechanisms to achieving this vital initiative using the Islamic benevolent loan “Alqard al-hasan.”